The principles of the development of future computer science teachers’ cognitive activity in the process of training in mathematics - Fomenko, L. (Problems of Engineer-Pedagogical Education, 2019)
The article deals with the problem of the development of cognitive activity of future computer science teachers and focuses on the need to reconsider the tasks and the content of their professional training regarding the reformation of the national educational system and taking into account the rapid growth and extensive use of information technology in almost all areas of human activity. Aiming at developing students’ cognitive activity, the author suggests using the potential of training in mathematics as a component of professional training, since cognitive methods and means used in mathematics are universal, so they can be used by students both while studying academic disciplines envisaged by the educational program, and in their further professional-pedagogical activity. The article substantiates that for the effective development of cognitive activity of future computer science teachers it is necessary to use general didactic guidelines, especially the principles of fundamentalization of education, orientation of education towards future professional activity, individual approach and subject-subject interaction between teachers and students, as well as problem-solving and cognitive visualization principles.